2002
DOI: 10.4049/jimmunol.168.11.5397
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Immune Cells as Sources and Targets of the IL-10 Family Members?

Abstract: This study investigated the expression of five novel human IL-10-related molecules and their receptors in blood mononuclear cells. IL-19 and IL-20 were found to be preferentially expressed in monocytes. IL-22 and IL-26 (AK155) expression was exclusively detected in T cells, especially upon type 1 polarization, and in NK cells. IL-24 (melanoma differentiation-associated gene 7) expression was restricted to monocytes and T cells. Detection of these molecules in lymphocytes was predominantly linked to cellular ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
545
3
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(578 citation statements)
references
References 14 publications
26
545
3
4
Order By: Relevance
“…6,7 has been found to be preferentially expressed in monocytes and its main targets are keratinocytes, where IL-20 binds type I IL-20R (IL-20Ra and -20Rb) and type II IL-20R (IL-20Rb and -22R) complexes. 6,8,9 Binding of the IL-20 in human HaCaT keratinocytic cell line results in STAT 3 phosphorylation and activation of a promoter including STAT-binding sites. 6 Microarray and RT-PCR analyses in HaCaT cells have demonstrated that the expression of several genes involved in inflammation are increased in response to IL-20 and therefore this cytokine may modulate the inflammatory response in the skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 has been found to be preferentially expressed in monocytes and its main targets are keratinocytes, where IL-20 binds type I IL-20R (IL-20Ra and -20Rb) and type II IL-20R (IL-20Rb and -22R) complexes. 6,8,9 Binding of the IL-20 in human HaCaT keratinocytic cell line results in STAT 3 phosphorylation and activation of a promoter including STAT-binding sites. 6 Microarray and RT-PCR analyses in HaCaT cells have demonstrated that the expression of several genes involved in inflammation are increased in response to IL-20 and therefore this cytokine may modulate the inflammatory response in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…IL-19 has been detected in immune cells, such as LPS-or GM-CSF-activated and resting monocytes, and at lower level in resting and stimulated B cells. 7,8 This cytokine binds to the type I IL-20R complex and modulates gene expression in responsive cell types through activation of the STAT 1 and STAT 3 signal transduction pathway. [9][10][11] Sharing the same receptor complex with IL-20 suggests that IL-19 may have partially overlapping biological activities with IL-20.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The expression levels of IL-19, IL-20 and IL-24 in lesional skin of psoriasis patients are increased compared to healthy skin. 2,[7][8][9][10][11] Two independent studies have demonstrated that overexpression of IL-20 in transgenic mice induces a skin phenotype similar to psoriasis. 2,5 Both in vitro and in vivo, IL-20 promotes hyperproliferation and abnormal differentiation of keratinocytes that are characteristic features of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…10 Once bound, IL-24 signals through the heterodimeric receptors, leading to the phosphorylation and activation of the JAK/ STAT pathway. 10,12 In contrast to the IL-10 receptor (IL-10R1/IL-10R2), which is constitutively expressed by most hemopoietic cells, 14 constitutive expression of the IL-24 receptors (IL-20R2 with at least one of the R1 chains) was not found in the immune cells tested, 11 but was detected in various nonhemopoietic tissues including lung, testis, ovary and skin, indicating a pleotropic role of IL-24 outside of the immune system. 15 Human IL-24 gene originally was known as mda-7 (melanoma differentiation associated gene-7), which was identified by subtraction hybridization as a gene whose expression was upregulated in H0-1 melanoma cells when the cells were induced to terminal differentiation by the combination of IFN-b and mezerein.…”
Section: Introductionmentioning
confidence: 99%
“…7 Expression of IL-24 was detected in spleen, thymus, 8 melanocytes, 9 ConA activated human PBMC cells, 10 LPS-treated monocytes and anti-CD3-treated T cells. 11 Two heterodimeric receptors for IL-24 have been identified, IL-20R1/IL-20R2 and IL-22R/IL-20R2, 10,12 the subunits of which belong to the class II cytokine receptor family. 13 IL-24 can bind to the IL-20R2 subunit alone, but co-expression of either IL-20R1 or IL-22R not only increases the binding affinity but also is necessary for receptor activation.…”
Section: Introductionmentioning
confidence: 99%